The Social Identity of Football Supporters in Providing Sportive Support to Arema Plajk;.yer (a Phenomenology study to supporter of aremania in Malang). - Doewes, Rumi Iqbal; Riyadi, Slamet (Proceeding of International Conference on Teacher Training and Education, 2016)
Aremania is a supporters group for Arema Malang Club. Aremania is a group of highly complexphenomenon. Social identity Aremania as a group or community to make them different from other supporters groups in Indonesia. Aremania formed in the mid 90s in the harsh social context because of thepresence of youth gangs that time. However, Aremania finally able to get public sympathy in Malang andIndonesia as supporters who have an image of manners and sportsmanship in expressing support, isevidenced by the title of the best fans in 2005, 2006 and 2013. Aremania also arise in the context of theinstitutionalization political culture fans, but once again Aremania answer with culturally-based groups withno institutional. This study carried to know the construction of social identity in the context of the history. Inaddition, this study aims to know how the Aremania supporters represents sportsmanship to athletes. Thisstudy used qualitative methods. The approach used was phenomenology.